Proteomic analysis of the fish pathogen Flavobacterium columnare - GÜLSOY, NAGİHAN (BIOMED CENTRAL LTD, 2010)
Background: Flavobacterium columnare causes columnaris disease in cultured and wild fish populations worldwide. Columnaris is the second most prevalent bacterial disease of commercial channel catfish industry in the United States. Despite its economic importance, little is known about the expressed proteins and virulence mechanisms of F. columnare. Here, we report the first high throughput proteomic analysis of F. columnare using 2-D LC ESI MS/MS and 2-DE MALDI TOF/TOF MS. Results: Proteins identified in this study and predicted from the draft F. columnare genome were clustered into functional groups using clusters of orthologous groups (COGs), and their subcellular locations were predicted. Possible functional relations among the identified proteins were determined using pathway analysis. The total number of unique F. columnare proteins identified using both 2-D LC and 2-DE approaches was 621, of which 10.95% (68) were identified by both methods, while 77.29% (480) and 11.76% (73) were unique in 2-D LC and 2-DE, respectively. COG groupings and subcellular localizations were similar between our data set and proteins predicted from the whole genome. Twenty eight pathways were significantly represented in our dataset (P < 0.05). Conclusion: Results from this study provide experimental evidence for many proteins that were predicted from the F. columnare genome annotation, and they should accelerate functional and comparative studies aimed at understanding virulence mechanisms of this important pathogen.
Keywords: CATFISH ICTALURUS-PUNCTATUS; PROTEIN SUBCELLULAR-LOCALIZATION; MICROBIAL GENE IDENTIFICATION; TROUT ONCORHYNCHUS-MYKISS; POLYMERASE-CHAIN-REACTION; AC LYASE ACTIVITY; ESCHERICHIA-COLI; FLEXIBACTER-COLUMNARIS; CHANNEL CATFISH; OUTER-MEMBRANE